Optimalisasi Komunikasi Organisasi Pada Perusahaan di Masa Pandemik Covid-19 (Approaches and Processes: Katherine Miller) - Devy Putri Kussanti (LPPM Universitas Bina Sarana Informatika, 2020)
If a company or agency is faced with a conflict, the thing that must be done is not to avoid conflict but to manage conflict, conflict can be faced and managed by knowing in advance where the cause is and also understanding how to solve existing problems. A leader must be able to provide a good role model in terms of communication and action. In addition, a leader must also swiftly solve problems by managing conflict. Some communication measures used are to communicate as well as possible both vertically and horizontally to all levels in the company. Based on Katherine Miller's theory, it can be studied more deeply about how a leader should manage conflict properly and correctly. Through optimization in organizational communication, especially during the Covid-19 pandemic, the contribution of a leader in a company will be seen. So the importance of leadership style in a company is a step towards the success of a company. Keyword: Communications and Leadership Style